P18 An evaluation of paracetamol prescribing across the child health wards to ensure optimal analgesia whilst avoiding toxicity following recent changes to maximum daily doses. Issue 2 (19th January 2018) - Cheung, Sharon; Haley, Helen
Abstract : Aims: To evaluate paracetamol dosing in paediatric patients against local 1 and BNFc 2 guidance following advice that toxicity can rarely occur with doses exceeding 75 mg/kg/day. Secondly to determine adherence to regular paracetamol prescriptions to establish the impact of analgesia by reviewing Wong and Baker pain assessment. 3 Method: The drug charts of all paediatric inpatients on five separate days were retrospectively reviewed to identify patients prescribed paracetamol for analgesia. The drug charts were scrutinised to determine if any doses of paracetamol prescribed potentially exceeded 75 mg/kg/day. The doses, routes, frequencies, and doses in mg/kg of paracetamol prescribed were recorded. The number of regular paracetamol doses administered was compared against the prescribed frequency and the numbers of regular doses omitted with and without documented reason were recorded. The comfort round sheets were reviewed to establish if the Wong and Baker pain assessment 3 were used to assess pain and results obtained before and after the first 24 hour period of regular paracetamol treatment were recorded where available. Results: 75 paediatric patients prescribed paracetamol for analgesia were identified over data collection period, approximately 50% split surgical: medical. One patient had no dose frequency of paracetamol prescribed hence the data of a total of 74 paediatric patients was analysed. 78% of paediatric patients were prescribed paracetamol for use when required; in surgery 40% were prescribed regular paracetamol compared with 9% in medicine. Overall, 74% of paediatric patients were prescribed paracetamol at a dose of 15 mg/kg and at a frequency of QDS in line with local guidance. 1 Equally distributed across both medical and surgical wards, 11% of patients were prescribed doses of paracetamol potentially exceeding 75 mg/kg/day as no maximum frequency stated when prescribed 4–6 hourly prn. One surgical patient was prescribed 20 mg/kg QDS regularly hence exceeding the recommended 75 mg/kg/day, this was changed by the prescriber. 16 paediatric patients were prescribed paracetamol as a regular medicine but 31% of these patients had one or more missed doses without any reason for omission documented on the drug charts. Patients who had omitted doses who had a corresponding Baker Wong pain score indicated little or no pain hence omission was appropriate although not adequately documented. Conclusions: The majority of patients were prescribed paracetamol at the 15 mg/kg dose 4–6 hourly in keeping with the local guidance 1 for inpatients but there was potential to administer up to 90 mg/kg/day when the prescribers did not specify a maximum frequency QDS. One surgical patient had been prescribed 20 mg/kg QDS which was an overdose in relation BNFc 2 guidance indicating a training requirement for the surgical and anaesthetic teams. The pain assessment tool was not consistently being used to evaluate analgesia and missed doses of analgesia were not being recorded appropriately. A key message was issued to all teams to emphasise the recommended paracetamol dose and monitoring required ensuring adequate analgesia whist highlighting the need to review regular paracetamol prescriptions daily. References: Bedside Clinical Guidelines Partnership and Partners in Paediatrics. Paediatric guidelines 2014;(6). Stoke-on-Trent: Bedside Clinical Guidelines Partnership. Royal Pharmaceutical Society. British national formulary for children – September 2015 – 2016 2015. London: BMJ Group and the Royal Pharmaceutical Society. Wong DL, Hockenberry-Eaton M, Wilson D, Winkelstein ML, Schwartz P. Wong's essentials of paediatric nursing (6th ed.) 2001. St. Louis: Mosby.